Interference and the Translation of Phraseological Units in a Parallel and Multilingual Corpus - Sanz-Villar, Zuriñe (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2018)
This paper will report on findings obtained from a corpus-based translation analysis of phraseological units on texts translated from German into Basque, with special emphasis placed on the shape that interference (Toury 1995/2012) takes in German-into-Basque literary translations. It will be shown not only that “typical” source language interference can be found in translated texts, but also that interference arises from other texts and/or languages present in the translator’s mind, most commonly in this study; Spanish. For the purpose of carrying out such an analysis, a digitized, parallel and multilingual corpus was compiled consisting of German source texts (STs), Basque target texts (TTs) and their corresponding intermediary versions in cases of indirect translation.